Better be careful: The replenishment of ABS backed by SME loans - Arved Fenner; Philipp Klein; Carina Mössinger (Deutsche Bundesbank, 2021)
We investigate the replenishment of 102 asset-backed securities (ABS) backed by more than 1.7 million small- and medium-sized enterprise loans. Based on our extensive data set from 2012 to 2017 obtained from the first and only central loan-level repository for ABS in Europe, we reveal that loans added to securitized loan portfolios after the transactions' closing perform worse than loans that are part of the initial portfolio. On average, we find that loans added to securitized loan portfolios demonstrate a 0.42 percentage points higher probability of default. We additionally provide evidence that originators induce these performance differences since they exploit their information advantage by deliberately adding low-quality loans to securitized loan portfolios. This adverse behavior is mitigated by originators' reputation efforts, by increasing transparency in the ABS market, as for example per the European Central Bank's loan-level initiative, and most effectively by their interaction.
Keywords: G11; G21; G23; 330; ABS; Agency Conflicts; Portfolio Replenishment; Securitization; SME